2 µm vector mode-locked pulses from Tm:Y2O3 ceramics laser. (27th February 2019) - Zhou, Wei; Huang, Haitao; Chen, Xiang; Wang, Jingru; Xu, Rui; Wang, Haotian; Zhao, Yongguang; Tang, Dingyuan; Wang, Yishan; Shen, Deyuan
Abstract: We report on stable passively mode-locked (ML) pulses with Tm:Y2 O3 ceramics operating at a 2 µ m wavelength range for the first time. With a SESAM, synchronous ML pulses with dual-wavelengths are obtained, with a typical pulse width of 40 ps, a maximum output average power of 240 mW and a pulse repetition rate of ~124 MHz. The output pulses were further proved to be stable polarization-locked vector pulses. To our knowledge, this is also the first observation of vector pulses in 2 µ m ML solid-state oscillators.